PENGARUH ADMINISTRASI PENDIDIKAN DAN KINERJA GURU TERHADAP DISIPLIN BELAJAR DI SMK IT IBNU KATSIR JEMBER - Arifin, Muhammad Zainol; Neviyani, Neviyani; Andrie W, Shendy (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
This study aims to evaluate the impact of Educational Administration and Teacher Performance on Student Discipline at SMK IT Ibnu Katsir Jember. Using a quantitative approach with an analytical survey and cross-sectional design, the research sample consists of 31 students from grades X and IX. Data analysis was performed using multiple regression and hypothesis testing. The findings indicate that Educational Administration (X1) has a negative effect on Student Discipline (Y), with a significance value of 0.916 (greater than α = 0.05) and a t-value of -0.107 (less than the t-table value of 2.048). Conversely, Teacher Performance (X2) positively and significantly affects Student Discipline, with a significance value of 0.004 (less than α = 0.05) and a t-value of 3.432 (greater than the t-table value of 2.084). Additionally, both Educational Administration and Teacher Performance together have a positive effect on Student Discipline, as indicated by a significance value of 0.003 (less than α = 0.05) and an F-value of 10.721 (greater than the F-table value of 3.33). This study highlights the critical role of Teacher Performance in enhancing Student Discipline, while Educational Administration does not show a significant impact on its own.